Relationship between intracellular calcium and morphologic changes in rabbit erythrocytes: Effects of the acylated and unacylated forms of E. coli alpha-hemolysin - Vázquez, Romina Florencia (2016)
Alpha-hemolysin (HlyA) is a hemolytic and cytotoxic protein secreted by uropathogenic Escherichia coli strains, whose expression correlates with the severity of the infections produced. HlyA is synthesized as a protoxin, ProHlyA, that becomes matured to the active form in the cytosol by hemolysin-C-directed fatty acylation at the ϵ-Amino residues of Lys 564 and Lys 690, before export from the toxin-producing bacteria. This posttranslational modification is remarkable because the nature of the protein is changed by the lipidic moiety from a benign protein to a frank toxin. In the present work, we demonstrated for the first time that, despite being hemolitically inactive, ProHlyA induced cellular morphologic changes in rabbit erythrocytes. A discocyte-to-echinocyte transformation was triggered by the protoxin in the absence of any accompanying increase in intracellular-Ca2 + levels. In addition, the Ca2 +-influx kinetics in HlyA-treated erythrocytes indicated that the active toxin induced an elevation in intraerythrocyte-Ca2 + content in a biphasic manner, with an initial rise in Ca2 + that depended on the association of the protein with the target membrane and a second increment corresponding to an activation of purinergic channels. The first increase was sufficient to trigger a discocyte-echinocyte-spherocyte transition in erythrocyte shape, though the subsequent rise mediated by purinergic signalling was essential for the occurrence of hemolysis. The results presented here provide new insights into the mechanism of action of this toxin.